Utilização do meloxicam para reduzir respostas Inflamatórias em bovinos de corte transportados - Guarnieri Filho, Thomaz Antonio [UNESP] (2015)
This experiment evaluated the effects of meloxicam administration on physiological and performance responses of transported cattle during feedlot receiving. Eighty-four Angus × Hereford steers were ranked by BW on d -10, and assigned to 21 dry lot pens. From d -10 to 0, pens were fed Alfalfa-grass hay ad libitum and 2.4 kg/steer daily (DM basis) of a corn-based concentrate. On d 0, pens were randomly assigned to: 1) transport for 1,440 km in a livestock trailer and oral administration of meloxicam (1 mg/kg of BW) at loading (d 0), unloading (d 1), and daily from d 2 to 7 of feedlot receiving (MEL; n = 7), 2) same transportation and treatment schedule of MEL, but oral administration of lactose monohydrate (1 mg/kg of BW) instead of meloxicam (TRANS; n = 7), or 3) no transport and oral administration of lactose monohydrate (1 mg/kg of BW) concurrently with treatment administration to MEL and TRANS (CON; n = 7). Upon arrival (d 1), MEL and TRANS steers returned to their pens for a 21-d feedlot receiving with the same diet offered from d -10 to 0. Treatments were administered to steers via oral drench on d 0 and 1, or mixed daily with the concentrate from d 2 to 7. Full BW was recorded prior to (d -2, -1, and 0) treatment application and at the end of experiment (d 20, 21, and 22) for ADG calculation. Daily DMI was recorded from d 1 to 21. Blood samples were collected on d 0, 1, 3, 5, 7, 10, 14, and 21. During the initial 7 d of feedlot receiving, hay and total DMI were reduced (P ≤ 0.03) in TRANS vs. CON and MEL, similar between CON and MEL (P ≥ 0.26), whereas concentrate DMI did not differ (P = 0.16) among ...